Community based water management and social capital - Kobayashi, Kiyoshi 1953- (IWA Publishing, 2014)
Community Based Water Management and Social Capitalprovides scientific understanding of community based water management and how to secure responsible management to satisfy quality and quantity requirements. It shows how community based water management can be synchronized with public water service, by introducing the most recent field experiments and theoretical studies in economics, social science, engineering, and regional planning which include game theory, microeconomics, econometric, statistics, social network analysis, social choice, and micro finance. Community Based Water Management and Social Capital presents field experiments and theoretical studies in economics, social science, engineering, and regional planning to investigate important questions: what motivates people involve in voluntary water management what is the effect of participatory approach in water management how does social capital work in the voluntary actions what are key factors for effective governance for water management with diverse actors - local people, enterprise, and government; what is necessary for proper water allocation; vi) how to synchronize public water service with community based water management. The book provides students, researchers, practitioners and governments with a comprehensive account of the current situation and perspectives on voluntary water management. It delivers a new scientific understanding on sustainable water management schemes and appropriate institutional social structures to secure inalienable rights to access to water.